Zonasi Konservasi untuk Siapa? Pengaturan Perairan Laut Taman Nasional Bali Barat - Mahmud, Amir; Satria, Arif; Kinseng, Rilus A. (Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
The zoning is not as usual and natural issues but complicated processes that determines allowed and prohibited activities of resources user. From economic views, zonation could potentially take advantages and disadvantages, and socially it create a conflict as consequence of limited accesses. This research as qualitative research aims to observe zones utilization and it impacts to marine resource users in Bali Barat National Parks (BBNP). The results show that utilization of marine zoning in BBNP is to ecology-biology protection, tourist and fisheries with resources user namely Boarding of BBNP, tourist company and fishers. Zoning results in regulating user activities including limited activities.